2022
DOI: 10.7150/ijms.71648
|View full text |Cite
|
Sign up to set email alerts
|

The role of circular RNA in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DKD) is the most common chronic microvascular complication of diabetes. About 20%-40% of diabetics develop DKD, which eventually leads to chronic kidney failure. Although progress has been made in diagnosis and treatment tools, diabetic nephropathy is still a major clinical problem. In recent years, circular RNA (CircRNA) has become a research hotspot. CircRNA is a non-coding RNA formed by covalently closing the 5 'and 3' ends of the precursor RNA. CircRNA has powerful biological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Although previous studies on diabetic nephropathy had the limitation of being restricted to animal experiments, the findings suggest that the circRNA_0001946–miR671-5p–CDR1 axis is a potential therapeutic target for diabetic nephropathy. Findings on other circRNA–miRNA axes such as circRNA_15698–miR-185 also suggested that miRNA regulation may trigger diabetic nephropathy or be involved in the progression of diabetic nephropathy [ 31 , 32 , 33 ]. On the other hand, Hsa_circ_0054633 were also shown to be useful as diagnostic markers of pre-diabetes and type 2 diabetes mellitus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies on diabetic nephropathy had the limitation of being restricted to animal experiments, the findings suggest that the circRNA_0001946–miR671-5p–CDR1 axis is a potential therapeutic target for diabetic nephropathy. Findings on other circRNA–miRNA axes such as circRNA_15698–miR-185 also suggested that miRNA regulation may trigger diabetic nephropathy or be involved in the progression of diabetic nephropathy [ 31 , 32 , 33 ]. On the other hand, Hsa_circ_0054633 were also shown to be useful as diagnostic markers of pre-diabetes and type 2 diabetes mellitus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These biomolecules—transported by macrovesicles, exosomes, and transmembrane proteins—are involved in the regulation of different pathways promoting fibrosis and inflammation especially in the heart and the kidney [ 12 , 20 , 24 ]. As the lack of influence of glomerular filtration on their urinary levels unlike serum creatinine [ 49 ], miRNAs can be used as innovative biomarker for DN even at the preclinical stage [ 25 , 27 , 28 ].…”
Section: Evidence On the Role Of Mirnas -21 -126 -216 And -377 In Dn ...mentioning
confidence: 99%
“…Besides classical markers (e.g., urinary cystatin C) [ 10 , 19 , 20 , 21 ], novel promising options are emerging in this research area [ 14 , 20 , 22 ]. In this framework, a pathogenic role for microRNAs (miRNAs) as biomolecules regulating up to 30% of the protein-coding genes in the human genome has been also proposed [ 23 , 24 , 25 , 26 ]. To date, miRNAs represent the most attractive candidates as potential diagnostic, prognostic, and therapeutic DN tool [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of the complex cellular and molecular events could help us to improve antifibrotic therapies for renal fibrosis. Accumulating evidence has implicated circRNAs in the pathogenesis of renal fibrosis [ 77 , 78 ]. For instance, circ_0000064 is upregulated in mesangial cells from high glucose (HG)-induced renal fibrosis and in kidneys from patients with diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%